Influence de la préparation physique sur les relations interpersonnelles?: Une étude exploratoire - Relave, A.; Campo, M.; Nicolas, M. (Movement & Sport Sciences - Science & Motricité, 2019)
Physical conditioning can be considered in different forms: specific, semi-specific or integrated. Each of them has physiological advantages and disadvantages; the aim of this study was to explore emotional experience and interpersonal relationships effects according to three forms. Ten rugby players, aged between 16 and 18 years (M = 16.90, SD = 0.74), participated in this exploratory qualitative study. From self-confrontational interviews following a physical conditioning training with three forms, tendencies have been identified in regards with emotional experience and interpersonal relationships. These tendencies would seem to show that physical conditioning, through three forms associated with different emotional process, could enhance emotional sharing and, in this way, interpersonal relationships among young elite players.